Identifying the Aspects and Components Impacting on Enterprise Resources Planning (ERP) Utilization with Human Resources Empowerment Approach in Education - et. al., Shapoor Etehadnezhad , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Enterprise resources planning system and its impact on empowerment of human resources, as the most valuable asset of any enterprise, is not something to be overlooked. The purpose of this research was to identify the aspects and components impacting on enterprise resources planning system utilization with the approach of human resources’ empowerment in Education. A questionnaire was used to collect data and identification of the relevant components was made by thematic analysis method. The statistical population of this research include practitioners and managers of information technology and human resources of General Office for Education of Fars province and sampling method is cluster random. As a result of analysis, the components of enterprise resources planning system include organizational strategy and policy, organizational breadth and complexity, business processes, management-communications and organizational culture, human resources, skill and empowerment, shared values and beliefs, and aspects of human resources empowerment are: capability, independence, influence and role play, worth, trust and honesty.